Carbamylation/citrullination of IgG Fc in bronchiectasis, established RA with bronchiectasis and RA smokers: a potential risk factor for disease. Issue 3 (19th September 2017) - Hutchinson, David; Clarke, Alexander; Heesom, Kate; Murphy, Daniel; Eggleton, Paul
Bronchiectasis (BR) and smoking are risk factors for rheumatoid arthritis (RA) development. The mechanisms by which smoking and BR trigger RA are unknown, but are associated with concurrent rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibody (anti-CCP) positivity. Anti-carbamylated protein antibodies (anti-CarP) have also been observed in BR patients and can be induced by smoking. Given that RF only has one antigen, immunoglobulin G (IgG) we have suggested that post-translational modifications to the Fc region of the heavy chain of IgG (IgGH) are a potential explanation for the clustering of the RA-associated autoantibodies in RA. Protein analysis was undertaken on 22 individuals. Four of the individuals had a diagnosis of BR at the time of protein analysis and subsequently developed RA up to 18 months following blood sampling. Four smoking RA patients and 4 patients with both BR and RA and 10 healthy controls were also studied. We identified modified arginines (Arg) frequently in the variable region and CH3 domains of IgG in patients and control subjects alike, but only observed carbamylated Lys and/or citrullinated Arg modifications in the RF binding site of the IgG CH2 domain of 5/12 (41.7%) patients investigated (1 BR, 2 RA and 2 BRRA), but in no control subjects (0/10, 0%) p=0.02. This is the first report of citrullination and carbamylation at the RF binding site of IgG in RA. These results point towards the concept of a universal antigen in RA, an antigen that is post-translationally modified at the Fc region of IgGH. Fc region of IgG is citrullinated and carbamylated, and these PTMs can occur prior to the development of RA http://ow.ly/8ZDe30evfO4